Novel Role of IL (Interleukin)-1β in Neutrophil Extracellular Trap Formation and Abdominal Aortic Aneurysms. Issue 4 (April 2018) - Meher, Akshaya K.; Spinosa, Michael; Davis, John P.; Pope, Nicolas; Laubach, Victor E.; Su, Gang; Serbulea, Vlad; Leitinger, Norbert; Ailawadi, Gorav; Upchurch, Gilbert R.
Abstract : Objective—: Neutrophils promote experimental abdominal aortic aneurysm (AAA) formation via a mechanism that is independent from MMPs (matrix metalloproteinases). Recently, we reported a dominant role of IL (interleukin)-1β in the formation of murine experimental AAAs. Here, the hypothesis that IL-1β–induced neutrophil extracellular trap formation (NETosis) promotes AAA was tested. Approach and Results—: NETs were identified through colocalized staining of neutrophil, Cit-H3 (citrullinated histone H3), and DNA, using immunohistochemistry. NETs were detected in human AAAs and were colocalized with IL-1β. In vitro, IL-1RA attenuated IL-1β–induced NETosis in human neutrophils. Mechanistically, IL-1β treatment of isolated neutrophils induced nuclear localization of ceramide synthase 6 and synthesis of C16-ceramide, which was inhibited by IL-1RA or fumonisin B1, an inhibitor of ceramide synthesis. Furthermore, IL-1RA or fumonisin B1 attenuated IL1-β–induced NETosis. In an experimental model of murine AAA, NETs were detected at a very early stage–day 3 of aneurysm induction. IL-1β–knockout mice demonstrated significantly lower infiltration of neutrophils to aorta and were protected from AAA. Adoptive transfer of wild-type neutrophils promoted AAA formation in IL-1β–knockout mice. Moreover, treatment of wild-type mice with Cl-amidine, an inhibitor NETosis, significantly attenuated AAA formation, whereas, treatment with deoxyribonuclease, a DNA digesting enzyme, had no effect on AAA formation. Conclusions—: Altogether, the results suggest a dominant role of IL-1β–induced NETosis in AAA formation. Abstract : Supplemental Digital Content is available in the text.